The Influence of Drift Garage Content as an Automotive Influencer on Social Media on Interest in Buying Car Modification Products - josi Meilonita; Lilik Wahyudi (LP2M IAIN Palopo, 2026)
This study, entitled The Influence of Garasi Drift’s Content as an Automotive Influencer on Social Media toward Purchase Intention of Car Modification Products, aims to analyze the influence of Garasi Drift’s content as a Mega Influencer on consumers’ impulsive buying interest in automotive modification products. The research object consists of social media followers of Garasi Drift who actively engage with automotive-related digital content. This study employs a quantitative approach using an online survey method distributed to 250 respondents selected through purposive sampling. The collected data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the SmartPLS software. The findings indicate that the congruence between consumers, influencers, and products has a positive effect on impulsive buying intention, and the Wishful Identification factor strengthens this relationship. The study concludes that content created by mega automotive influencers such as Garasi Drift can shape consumer perception, emotional attachment, and stimulate spontaneous purchase behavior toward modification products. The results contribute theoretically to the development of digital marketing studies and provide practical implications for automotive brands and influencers in designing more effective communication and content strategies.